The Effect Of Product Quality, Price And Service Quality On Customer Satisfaction At Pondok Makan Bunda Niar Air Nelengau Seginim - Kurnia Dwi Ferli; Ahmad Soleh; Yun Fitriano (Penerbit Jurnal Indonesia, 2023)
The research aims to determine the effect of product quality, price and service quality on customer satisfaction at Pondok Makan Bunda Niar Air Nelengau Seginim. At the present time marketing using product quality improvement, affordable prices and quality service. This study uses quantitative research methods, the population in this study is consumers, through a given questionnaire. The technique in taking the research sample using the accidental sampling technique is a technique of determining a sample based on chance, the sample in this study was 80 customers at Pondok Makan Bunda Niar Air Nelengau Seginim. Data collection used instruments in the form of questionnaires and the analytical method used was multiple linear regression, determination test and hypothesis testing.The research aims to determine the effect of product quality, price and service quality on customer satisfaction at Pondok Makan Bunda Niar Air Nelengau Seginim. At the present time marketing using product quality improvement, affordable prices and quality service. This study uses quantitative research methods, the population in this study is consumers, through a given questionnaire. The technique in taking the research sample using the accidental sampling technique is a technique of determining a sample based on chance, the sample in this study was 80 customers at Pondok Makan Bunda Niar Air Nelengau Seginim. Data collection used instruments in the form of questionnaires and the analytical method used was multiple linear regression, determination test and hypothesis testing. Product quality research results (X1), show t count of 2.954 > t table 1.66140 with a significant level of 0.004 <0.050. So it can be concluded that the variable Product Quality has a positive and significant effect on Customer Satisfaction. This means the hypothesis is accepted. PRICE affects Customer Satisfaction. Price variable (X2), shows t count of 2.525 > t table 1.66140 with a significant level of 0.014 <0.050. So it can be concluded that the price variable has a positive and significant effect on customer satisfaction. This means the hypothesis is accepted. Service quality affects customer satisfaction. The price variable (X2), shows t count of 2.800 > t table 1.66140 with a significant level of 0.000 <0.050. So it can be concluded that the service quality variable has a positive and significant effect on customer satisfaction.